Effect of ashwagandha (Withania Somnifera) consumption on the selected physical fitness variables of male sprinters - Satpal Yadav (Türk Spor ve Egzersiz Dergisi)
The purpose of the study was to investigate the effect of ashwagandha (Withania Somnifera) consumption on the selected physical fitness variables of male sprinters. The total number of 20 male sprinters which equally divided 10 in each group i.e. experimental and control groups. The sample was belong to, who had participated at inter college level under Lakshmibai National Institute of physical education, North east regional center in the age group of 18 to 25 years. Ashwagandha medicine gives to 10 experimental groups for 12 week thrice a week of alternate days with milk. After the 12 weeks physical fitness test was taken on 20 male sprinters, experimental as well as control groups. In conclusion; keeping the results and discussion in view the conclusions drawn that the significant effect of Ashwagandha on sprinters related to their standing broad jump (Meters), 50 yard dash (Seconds), pull-ups (Minutes), sit –ups (Minutes), shuttle run (Second), 12- min. run/walk.